Level of knowledge of diabetic pregnant women about the pathology, signs and symptoms, alarm guidelines and treatment in a public hospital in Rosario during the period from October to November 2020. - Avilez , Romina Guadalupe; Ponti, Liliana; Gabini, Sebastián; Camats , Silvina (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
Gestational diabetes (GD) is a disease that increases the risk of suffering obstetric problems and developing post-pregnancy diseases in both mother and child. A descriptive and cross-sectional study was carried out with the aim of evaluating the level of knowledge of diabetic pregnant women about gestational diabetes in the Maternity Inpatient Ward of the Hospital Provincial del Centenario during the period October-November 2020. Seventeen pregnant women with a confirmed diagnosis of GD participated in the study, of whom 8 patients were receiving insulin treatment and 9 were not receiving insulin therapy treatment. Confidentiality of personal and collected information was assured. The survey technique was used through a self-constructed collection instrument. The participants were between 19 and 43 years old, 71% of them had a diagnosis older than 30 days. Family history predominated in both groups. Regarding knowledge of GD, a little more than half did not identify the symptoms. Non-insulinized patients knew treatment guidelines in 44% and insulinized patients in 25% of cases, 38% reduced treatment to insulin therapy. Only 3 patients were aware of alarm guidelines. Seventy-six percent always comply with the glycemic control prescription indicated by the physician and insulinized patients were more aware of postpartum control (reclassification). Health education is recommended as an essential nursing task to improve the management of the disease by the patients, favor adherence to treatment and control of complications